WTO--trade in services - Wolfrum, Rüdiger; Stoll, Peter-Tobias; Feinäugle, Clemens (Max Planck commentaries on world trade law ;, 2008)
With the establishment of the WTO, trade in services became part of the world trade order. This volume covers the core agreement, the General Agreement on Trade in Services (GATS) with annexes.